2022
DOI: 10.1111/jcal.12763
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the modality principle to support learning with virtual reality: An eye‐tracking and electrodermal activity study

Abstract: Background Virtual reality (VR) is considered a promising approach to support learning. An instructional design is essential to optimize cognitive processes. Studies show that VR has unique instructional and pedagogical requirements. Objectives To evaluate the effectiveness and applicability of the modality principle, which was previously validated in 2D classic multimedia, for learning with VR. The modality principle states that multimedia information presented as spoken narration is superior to on‐screen tex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 83 publications
(110 reference statements)
0
3
0
Order By: Relevance
“…As discussed above, results from studies on learning with visualizations do not necessarily provide evidence that an effect needs to be reproducible when learning in virtual reality (Liberman and Dubovi 2022 ). Thus, we need to be careful when attempting to transfer the results of the present studies to learning in virtual worlds.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As discussed above, results from studies on learning with visualizations do not necessarily provide evidence that an effect needs to be reproducible when learning in virtual reality (Liberman and Dubovi 2022 ). Thus, we need to be careful when attempting to transfer the results of the present studies to learning in virtual worlds.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a recent study found that instructional principles that have been well-established within other media do not necessarily need to be transferable to learning in virtual reality. Liberman and Dubovi ( 2022 ) established that simultaneously using multiple sensory modalities, in their case the visual and auditory senses to present text either as narration or on-screen, does not improve learning in virtual reality despite positive results of this approach for other types of media (Moreno and Mayer 1999 ). Thus, the remainder of this overview will be focused on learning with visualizations rather than with entire virtual environments.…”
Section: Introductionmentioning
confidence: 99%
“…An alternative to VR high-immersive training using a headset is low-immersive VR training, often called desktop VR. The low-immersive VR training is a cheaper alternative that only needs to display the virtual world on a computer monitor [31]. However, it does not ensure the measurement of a high range of parameters available in high-immersive training.…”
Section: Introductionmentioning
confidence: 99%